Application of vibration wave CT technology in the dynamic prediction of shock hazards - Yi, EnBing; Mu, ZongLong; Wang, Hao (Frontiers in Earth Science, 2023)
The vibration wave CT detection technology could be used for forecasting dynamic disasters such as coal and gas outburst and rock burst in coal mine, and could also be used for dynamic monitoring and warning of impact risk. Based on the positive correlation between stress and vibration wave velocity and the positive abnormal distribution of vibration wave velocity, the impact danger area could be determined. Two evaluation indexes on impact risk were constructed, which were the anomalous coefficient An and abnormal value Am of gradient variation coefficient (VG) of wave velocity. The critical values of the two indexes corresponding to the impact risk degree were given. And the field engineering practice was carried out by using the inversion results of vibration wave CT detection technology, and combined with the field engineering geological conditions, the impact risk area of F15-24080 working face was defined comprehensively. The results showed high precision of this CT detection technology. It could make dynamic prediction and evaluation of impact risk on site, and provide guidance and test for the formulation and implementation effect of pressure relief measures in high impact danger areas.